Genetic engineering of lignin biosynthesis to enhance plant traits: applications in bioenergy, agriculture, and industry- a review - Shaharuddin, Noor Azmi Bin; Chong, Yu Lok Yusuf; Azhari, Mohd Farhan; Hilman, Mohamad Shafek; Abdullah, Meilina Ong; Abdul Masani, Mat Yunus (The Malaysian Solid State Science and Technology Society (MASS), 2024)
Lignin is the second most prevalent metabolite in plants after cellulose. It is a complex polymer that functions as a "backbone" for plants, providing mechanical support for stability and acting as a defense mechanism against pathogens and pests. The production of lignin involves the phenylpropanoid pathway, which generates several natural compounds that can be found in plants, including those in the lignin biosynthetic pathway. Throughout the decade, the production of lignin has become a major topic in enhancing plant traits due to its unique properties. Genetic engineering has paved the way for researchers to study lignin more effectively, offering potential benefits for the production of crops with improved traits. Tools such as CRISPR/Cas9 and RNA interference (RNAi) technology have made lignin studies more efficient, helping industries like agriculture and bioenergy become more sustainable. This review highlights genetic engineering approaches to lignin biosynthesis and their applications in the bioenergy and agricultural industries.